From Delos to Delphi : a literary study of the Homeric Hymn to Apollo - Miller, Andrew M. (Mnemosyne, Supplements, 1986)
This detailed literary and rhetorical analysis of the Homeric Hymn to Apollo treats the poem as a unified work of art in which sophisticated poetic craftsmanship is put to the service of serious ethical thought. By means of parallels from Homer, Hesiod, and other Homeric hymns, as well as from later epideictic poetry and prose, the author seeks to show that the poet of the Hymn follows a coherent ''program'' whose intention is to praise Apollo from his birth on humble Delos to his establishment in a position of glory at Delphi. At the same time, the ''Delian'' and ''Pythian'' portions of the hymn are linked by a complex network of ideas bearing on the ethos of Apollo and the nature of his Delphic oracle. The study takes into account previous scholarship on the Hymn and provides appendices on ''The Question of Unity'' and ''The Cosmological Hierarchy and Apollo's Timai ''.